2007
DOI: 10.1007/s11706-007-0061-6
|View full text |Cite
|
Sign up to set email alerts
|

Aragonite observed in the prismatic layer of seawater-cultured pearls

Abstract: The prismatic layer is obviously different from the parallel layer in seawater-cultured pearls. X-ray diffraction (XRD), optical microscopy (OM) and micro-infrared (IR) spectroscopy have been applied to characterize the crystallized layers of high-and low-quality seawater-cultured pearls produced in South China. The result shows that the prismatic layer is not only composed of calcite as reported in previous researches. Three types of prisms were found in seawatercultured pearls: calcite prism, aragonite prism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 3 publications
0
15
1
Order By: Relevance
“…During the middle stages (days [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], the carbon content decreased, as did the organic matrix and the baseline Raman spectrum. In previous studies, the CaCO 3 first deposited on the nucleus was the aragonitic [29] or calcitic [30] prismatic layer found in the cross section of the pearl, and the nacreous layer then formed on the prismatic layer. In the early stages in our study, the CaCO 3 depositions were all aragonites.…”
Section: Discussion (A) the Pearl Formation Processmentioning
confidence: 90%
“…During the middle stages (days [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], the carbon content decreased, as did the organic matrix and the baseline Raman spectrum. In previous studies, the CaCO 3 first deposited on the nucleus was the aragonitic [29] or calcitic [30] prismatic layer found in the cross section of the pearl, and the nacreous layer then formed on the prismatic layer. In the early stages in our study, the CaCO 3 depositions were all aragonites.…”
Section: Discussion (A) the Pearl Formation Processmentioning
confidence: 90%
“…Some of the pearls had an extraordinarily thin prismatic layer ( Fig. 5(a)) [12] while the others did not have any prismatic layer at all (Fig. 4).…”
Section: Characterization Of the Internal Structure Of Seawater Pearlsmentioning
confidence: 99%
“…Thick prismatic layers are the most signifi cant characteristic of these prismatic pearls as the crystallizing layers are essentially composed of these prismatic layers ( Fig. 5(b),(c),(d)) [12] . The prisms in these prismatic pearls are thicker than the fi ne needle-like prisms found in high quality pearls.…”
Section: Low Quality Seawater Cultured Pearls Without Lustermentioning
confidence: 99%
See 1 more Smart Citation
“…In such pearls, the prismatic layer on the nucleus differs from that of shell with respect to the crystal habit (Komaru, Sato, & Inoue, ). For example, aragonite prismatic layers (Cuif et al, ; Ma et al, ), pseudo‐prisms (Pérez‐Huerta, Cuif, Dauphin, & Cusack, ) and prism‐like structures (Komaru et al, ; Wada, ) have been reported. Hereinafter, these columnar structures which resemble prismatic layer in pearls are together referred to as non‐nacreous structures (NNSs) in this study.…”
Section: Introductionmentioning
confidence: 99%